The Role of the Financial Services Authority (OJK) in Supervising Illegal Investments in Indonesia - Fitriyanti , Fadia; Hanifah, Ekky Wahdatul (Faculty of Law, Universitas Slamet Riyadi, 2023)
The purpose of this research is to deepen the extent to which the Financial Services Authority (OJK) has made laws and regulations to control illegal investments in Indonesia. The Financial Services Authority is an institution that regulates and supervises financial institutions in Indonesia. However, there are still many illegal or illegal investment activities in society. Monitoring and eradicating illegal investments in Indonesia is the responsibility of the Financial Services Authority. The purpose of this study is to determine the role of the Financial Services Authority in eradicating illegal investments in Indonesia. This type of research is a literature study with a qualitative approach because the data produced is in the form of words or descriptions. Sources of data were analyzed using time series data, library data collection methods and reading, recording and processing research materials. The population in this study is the analysis of related journals. The method used in this research is normative legal research.